Analisis Good Corporate Governance, Struktur Modal, Karakteristik Perusahaan terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Mediasi pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia - Cailah Nasywa Afrila; Hwihanus Hwihanus (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to investigate and evaluate the effects of capital structure, Good Corporate Governance, and company characteristics on company value, with financial performance serving as a mediating variable. The research applies a quantitative approach using secondary data obtained from mining companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The population of this study consists of all mining sector companies listed on the exchange, while the sample was selected using purposive sampling, resulting in 14 companies that met the established research criteria. Data analysis was conducted using SmartPLS to examine the direct and indirect relationships among the research variables. The findings indicate that capital structure, Good Corporate Governance, and company characteristics do not have a significant effect on either financial performance or company value. However, financial performance is proven to have a significant influence on company value. Furthermore, the results show that financial performance is unable to mediate the relationship between capital structure, Good Corporate Governance, and company characteristics on company value in mining sector companies during the observed period.